The Application of Extended Expectation-Confirmation Model to Identify Influencing Factors Digital Loyalty for Mobile-Based Travel Platform - Frans Sudirjo; Vivid Violin; Arnold Sultantio Hutabarat; Lely Indriani; Budi Utami (SEULANGA SYSTEM PUBLISHER, 2023)
The aim of this study was to determine the factors that impact the faithfulness of users on digital travel platforms, using the model proposed by researchers on satisfaction and loyalty based on user perceptions using the Expectation-Confirmation Model, which was enhanced by incorporating the variables of security and loyalty. Surveys were distributed online using a purposive sampling technique, and the minimum number of samples was determined using the Slovin formula with a 5% confidence interval. Subsequently, the data collected was analyzed using Ms. Excel and the PLS-SEM approach with SmartPLS. According to the findings of this study, out of the seven hypotheses, two hypotheses from travel A and B were rejected, specifically the security hypothesis regarding satisfaction and the satisfaction hypothesis regarding continuance intention. Similarly, the perceived usefulness hypothesis regarding continuance intention was rejected for travel A and B due to the path coefficient value and t-test of the hypothesis being less than 0.1 and 1.96. However, four hypotheses were accepted for all three platforms. According to the calculation of R2, satisfaction, continuance intention, and perceived utility are the three criteria that have the most impact on loyalty on the three digital travel platforms.